Lack in the Psychoanalytic Tradition - Lagidze, Nato; Chitashvili, Marine (Georgian Psychological Journal, 2026)
The article discusses the concept of lack in the psycho-dynamic tradition as an intrapsychic and interpsychic dynamic force that drives a constantly active desire, participates in identity formation, and produces the feeling of alienation. The article combines the perspectives of the representatives of the classical and contemporary, post-structuralist approaches in psychoanalysis and conceptualizes the notion of lack within different psychoanalytic models. The function of lack is discussed in the context of the individual’s perception of reality within intrapsychic and interpsychic dimensions based on the theories of Sigmund Freud, Jacques Lacan, Julia Kristeva, and Adam Phillips. In the intrapsychic realm, the primary function of lack relates to fundamental needs and aims to maintain desire in permanently active state. Desire, on its part, arises after transitioning from the imaginary to the symbolic register as a result of separation from the mother, which leads to alienation from oneself. In the interpsychic realm the sense of lack extends beyond the psyche into cultural and social dimensions and becomes the source of agency that drives the individual towards personal growth, self-reflection, and creative self-expression. The alienation resulting from lack bares both negative and creative potential for the psyche. The present article describes how sublimation, the overcoming of fantasy, and the symbolization of “inner foreignness” facilitate coping with the internal conflict and frustration caused by lack. In the concluding section, the article discusses potential ways of overcoming the sense of lack.